Pathogenic autoantibodies to neuronal proteins in neurological disorders. - Vincent, A; Lily, O; Palace, J (1999)
Autoantibodies to acetylcholine receptors and to voltage-gated calcium and potassium channels are thought to be pathogenic in three peripheral neurological disorders: myasthenia gravis, the Lambert Eaton syndrome and acquired neuromyotonia. However, evidence for the role of antibodies in conditions involving the central nervous system, is scanty or unclear. This review describes the ways in which the roles of autoantibodies have been defined in the peripheral diseases, and discusses the more controversial evidence for involvement of autoantibodies in some central disorders such as multiple sclerosis.